유한평판 및 T-joint 필렛 용접부에 있어서 3차원 표면균열의 피로 파괴거동에 관한 실험적 연구 - 한문식(M. S. Han); 김재동(J. D. Kim); 이호섭(H. S. Lee) (大韓造船學會 論文集, 1991)
Fatigure crack growth from surface defects is one of the most important subjects for the evaluation and the assurance of safety in pressure vessels, piping systems, ship hulls and other various structures. This paper attempts to analysis some practical or general problems such as the estimation of crack growth life to penetrate the plate thickness, based on fatigure crack growth from a single surface flaw and the interaction of multiple flaws. An experiment on the coalescence of multiple undercuts was carried out under cyclic tension condition as a attempt to the analysis of multiple crack problems. It is noted that the fracture strength is characterized by the analogy to that in a single crack growth. 최근 압력용기, 고압배관, LNG Tank 및 선체등의 구조물 파괴에 대한 안전성을 보증하기 위하여, 구조부재의 표면결함에 대한 균열성장 거동을 파악하는 것이 중요한 과제중에 하나라고 인식되어지고 있다. 본 연구에서는 단일 및 복수표면 결함의 피로균열 성장을 바탕으로 표면에서 관통되기까지의 균열성장 수명의 추정등 실질적이고 일반적인 문제들을 해석할려고 시도하였다. 또한, 복수균열 문제에 적용하기 위하여 복수 언더컷의 합체진전현상을 검토하였으며 단일 언더컷과 복수 언더컷의 전파특성이 유사함을 밝혔다.